Portal and mesenteric vein thromboses in a patient with prothrombin G20210 mutation, elevated lipoprotein (a), and high factor VIII - Hirmerova, Jana; Liska, Vaclav; Mirka, Hynek; Chudacek, Zdenek; Treska, Vladislav (Clinical and applied thrombosis/hemostasis, 2008)
A 65-year-old man was examined for abdominal pain. Portal and mesenteric vein thromboses were described by ultrasound and computed tomography. No local cause was found. The patient had a positive history of venous thromboembolism. Thrombophilia workup revealed prothrombin G20210A mutation (heterozygous), C677T mutation of methylenetetrahydrofolate reductase gene (homozygous), elevated level of lipoprotein (a), and high level of coagulation factor VIII. Anticoagulation was started and planned for a long-term duration. The etiology of portal vein thrombosis is often multifactorial, with various combinations of systemic factors (inherited or acquired prothrombotic conditions) and local precipitating factors (inflammation, injury to the portal venous system, cancer of the abdominal organs, cirrhosis). The reported prevalence of hypercoagulable states in patients with portal vein thrombosis has been very heterogeneous so far. Some authors support a role of the prothrombin G20210A mutation. In the reported patient, this mutation was revealed in a combination with other hypercoagulable states.
Keywords: senioři; vena portae; protrombin; mužské pohlaví; mutace; Factor VIII; vena mesenterica; Portal Vein; žilní trombóza; ultrasonografie; Mutation; Humans; lipoprotein (a); Prothrombin; faktor VIII; Ultrasonography; Mesenteric Veins; Aged; Venous Thrombosis; lidé; Male; Lipoprotein(a)